2013
DOI: 10.4238/2013.november.22.4
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of gastrointestinal stromal tumors based on atomic force microscope analysis

Abstract: ABSTRACT. This study was designed to detect the stiffness of single living gastrointestinal stromal tumor (GIST) cells in vitro using an atomic force microscope as a probe tool. We determined that the stiffness of living GIST cells was 3913 Pa, the stiffness of the membrane was 642 Pa, and the stiffness of the cytoplasm was 17,550 Pa. For comparison, we also determined the stiffness of a normal stomach cell, which was 7374 Pa, and that of in vitro GIST cells after 2 h of exposure, which was 10,680 Pa. Measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…In addition, the morphological observations support this opinion experimentally, showing that the cancerous cells usually have decreased stress fibers [25,29,33,67,68], increased cortical actin [25,33], and more lamellipodia [26,65], which benefit the invasion of cells by decreasing adhesion with the substrate and increasing the contraction forces for deformation and protrusion [27,64]. Taking into account that the nuclei are usually softer in cells with higher motility [58] and that the cortex actin network is much softer than the stress fibers [41], it is reasonable to detect a lower Young's modulus in metastatic carcinoma cells.…”
Section: Data Volumementioning
confidence: 59%
See 2 more Smart Citations
“…In addition, the morphological observations support this opinion experimentally, showing that the cancerous cells usually have decreased stress fibers [25,29,33,67,68], increased cortical actin [25,33], and more lamellipodia [26,65], which benefit the invasion of cells by decreasing adhesion with the substrate and increasing the contraction forces for deformation and protrusion [27,64]. Taking into account that the nuclei are usually softer in cells with higher motility [58] and that the cortex actin network is much softer than the stress fibers [41], it is reasonable to detect a lower Young's modulus in metastatic carcinoma cells.…”
Section: Data Volumementioning
confidence: 59%
“…Based on the dimensions of cortical actin filaments, it was suggested that the Young's modulus detected in the first 100~200 nm of indentation refers to the reflection of the stiffness of cortical actin [30,39,40]. Additionally, the extremely soft AFM tip and low indentation force are also suggested in the detection of cortex stiffness [40,41]. Meanwhile, the micropipette aspiration assay can be an alternative method to determine the cortical tension of cells by measuring the force needed to aspirate a small surface area of the…”
Section: / 28mentioning
confidence: 98%
See 1 more Smart Citation
“…In general, endoplasmic reticulum (ER) stress, apoptosis induction, and cell cycle arrest can inhibit cell proliferation. Previous studies reported that Tan IIA may inhibit the growth and proliferation of various cancer cells, such as lung, breast, liver, leukemia, and colon cancer Chen et al, 2012;Zhao et al, 2013;Lu et al, 2018;Wang et al, 2018;Zhou et al, 2018). The ER stress response is usually defined as the unfolded protein response, which is an imbalance between the accumulations of unfolded or misfolded proteins in the ER lumen .…”
Section: Tan Iia Inhibits Tumor Cell Growth and Proliferationmentioning
confidence: 99%
“…However, preoperative information is not available during surgery, and the early-stage gastric cancer is located on the inner surface of the stomach wall and cannot be visually detected from the outside of the stomach. The surgeon's tactile sense can be used to locate the tumor, which has a different stiffness from the surrounding normal tissue [1], [2], [3]. However, input from the tactile sense is substantially limited in minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%